Between political cultures: the European elections and Portugal in time of crisis - Espirito Santo, Paula do (2015)
European elections are cyclic ally one of several barometers of how Europeans regard the dimension of the European project in their lives. Other indicators of the importance of the social dynamics of the EU are echoed among European citizens and voters. These indicators are reflected in terms of political participation and are closely related to European institutions such as the European Parliament, European Commission and European Central Bank, and the way they are experienced in every day democratic political expression, reflecting the civic dimension of political culture. The purpose and central challenge of this article is to contribute to an understanding of political culture in the European Union, in terms of electoral participation, especially in the aggravating circumstance of an economic crisis from 2008 onwards. This challenge is also faced more and more markedly at all times by the main political actors on the European stage, keepers and defenders of a long tradition of contemporary European thought, evoking the memory of Jean Monnet, Robert Schumann and Konrad Adenauer, to exalt some of its most prominent founding fathers. The main aim of this article is to contribute to reflection on the importance of voter participation in European political culture and achieve new levels of discussion and practical implementation of citizenship and civic inclusion. On the other hand, at a time when balancing the EU and keeping it running are serious, we also discuss their identity bases in terms of inclusion and political and electoral culture.